2011
DOI: 10.1371/journal.pbio.1001065
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Mycobacterial Growth and Antibiotic Sensitivity

Abstract: Treatment of chronic bacterial infections, such as tuberculosis (TB), requires a remarkably long course of therapy, despite the availability of drugs that are rapidly bacteriocidal in vitro. This observation has long been attributed to the presence of bacterial populations in the host that are “drug-tolerant” because of their slow replication and low rate of metabolism. However, both the physiologic state of these hypothetical drug-tolerant populations and the bacterial pathways that regulate growth and metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
280
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(306 citation statements)
references
References 34 publications
(46 reference statements)
20
280
0
1
Order By: Relevance
“…Despite intensive focus on the primary drug-target interaction and its maladaptive consequences, knowledge of the endogenous mechanisms used by bacteria to resist antibiotic activity is incomplete and centred chiefly around mechanisms associated with the drug-target interaction, such as drug efflux pumps and antibiotic-and/or target-modifying enzymes 3 . However, growing evidence has implicated a broader range of physiologic factors [7][8][9][10]27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite intensive focus on the primary drug-target interaction and its maladaptive consequences, knowledge of the endogenous mechanisms used by bacteria to resist antibiotic activity is incomplete and centred chiefly around mechanisms associated with the drug-target interaction, such as drug efflux pumps and antibiotic-and/or target-modifying enzymes 3 . However, growing evidence has implicated a broader range of physiologic factors [7][8][9][10]27 .…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have begun to revise this view with the demonstration that even non-, or slowly, replicating bacteria could be rendered sensitive to antibiotics. Studies of Escherichia coli, Staphylococcus aureus and even Mtb have shown that the activity of many antibiotics: (i) is dependent on the activity of specific metabolic pathways, (ii) differs for replicating and nonreplicating populations and (iii) can be dissociated from growth rate 7,12,27 . In Mtb, it was shown that adaptation to hypoxia was accompanied by a redirection of metabolic flux away from the TCA cycle and towards the generation of triglycerides, whose inhibition resensitized Mtb to antibiotics in absence of growth 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KstD has previously been shown to catalyze the ⌬ 1 -dehydrogenation of 4-AD, 6 5␣-androstane-3,17-dione, 5␣-testosterone, and progesterone (31). Monitoring of the reaction by HPLC revealed a decrease in the 4-BNC-CoA peak and appearance of a new peak eluting at 18 min of Gradient B.…”
Section: Production and Purification Of Steroid Coa Thioesters-twomentioning
confidence: 99%
“…Although the events which initiate dormancy are not fully understood, hypoxia, nitric oxide and nutrient starvation are among the factors believed to have prominent roles in initiating and maintaining dormancy (Betts et al, 2002;Voskuil et al, 2003;Wayne & Sohaskey, 2001). During dormant stages, the major sources of energy are host-derived cholesterol and triglycerides (Baek et al, 2011;Pandey & Sassetti, 2008). This study aimed to characterize the starvation-inducible, lipid-responsive transcription factor Rv0494 from M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%